Lines of Meaning Three calligraphic paintings by Didin Sirojuddin - Hooker, Virginia (Lajnah Pentashihan Mushaf Al-Qur'an, 2011)
This article analyses textual themes and images in three paintings by Didin Sirojuddin. The aim is to show the complex interrelationship between the written and painted elements of the works and the levels of rational and spiritual insight possible for the reader-viewers. Four aspects of the paintings have been selected for analysis: constituent elements; textual themes; visual images; and light.